Evaluating the efficiency of composting and vermicomposting for organic solid waste with the addition of biodegradable material - Barcia, Maiza Karine; Camargo, Giovani Almeida; Olivato, Juliana Bonametti; Martins, Kelly Geronazzo; Veiga, Tatiane Bonametti (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Improper disposal of solid waste leads to environmental and socioeconomic damages. In Brazil, approximately 45.3% of urban solid waste destined for landfills and "dumpsites" consists of organic waste, resulting in a reduced lifespan of sanitary landfills. This study aimed to analyze the efficiency of composting and vermicomposting processes for organic waste with the addition of biodegradable material. Composters were monitored for 100 days, analyzing physicochemical parameters such as temperature, pH, moisture, and organic matter. Microbial activity was also monitored through analysis of compost basal respiration, microbial biomass carbon, and metabolic quotient. Throughout the research, it was observed that temperature exhibited similar behavior during composting and vermicomposting. At the end of the process, composting pH showed better results; however, vermicomposting yielded more satisfactory results in terms of moisture and organic matter content. Microbial activity remained active, showing expected results, with a decrease in basal respiration rates and microbial biomass carbon, along with an increase in the metabolic quotient. After the study, it was concluded that the addition of biodegradable material did not interfere with the processes, demonstrating compostability potential. Thus, it was possible to ascertain that composting and vermicomposting techniques for organic solid waste, combined with the use of biodegradable material, contribute to the valorization of the circular economy, providing improvements for urban environmental sustainability.
Keywords: Organic waste; Waste Management; Composting; Vermicomposting